Group portrait of the attendees of the Old Timers Epworth League Institute training at Monte Toyon Camp - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait showing the attendees of the Old Timers Epworth League Institure training, held July 21-22, 1931 at Monte Toyon Camp. The group is assembled out of doors in front of a rustic cabin.